Thailand : Clean Energy for Green Low-Carbon Growth - World Bank Group (World Bank, Washington, DC, 2017)
Thailand needs to avoid the high-carbon growth path of many developed countries and, instead, take a low-carbon growth path. A green low-carbon growth path is in Thailand's own interest as it can simultaneously tackle local environmental degradation, global climate change, and energy security challenges. It can also position Thailand as a regional leader in green, sustainable growth. Green low-carbon growth in Thailand could focus on the following four pillars: 1) maintaining rapid economic growth while adjusting the country's economic structure toward a less energy, and carbon-intensive economy; 2) achieving greater urbanization while shifting toward green livable low-carbon cities; 3) meeting the huge thirst for energy while transforming the energy sector toward one of high energy efficiency and widespread diffusion of low-carbon technologies; and 4) improving quality of life while shifting toward a resource-efficient and sustainable lifestyle.